Working Rural Eco Tourism Planning in Yogyakarta Using MSP+DM Analysis - Priatmoko, Setiawan (E-Journal of Tourism; Volume 5 Number 1 (March 2018), 2018)
Ecotourism planning requires a systematic simple tool. This is because generally the actors of ecotourism in the region of Yogyakarta is a rural community activist which need a simple tools. Ecotourism activities are often associated with village tourism activities managed by the local community as community based tourism (CBT). Using MSP + DM analysis helps facilitate the planning and development of ecotourism for all stakeholders. Keywords: ecotourism, planning, rural, CBT, MSP+DM